PEMIKIRAN HADIS SYEIKH MUHAMMAD YASIN AL-FADANI - Saleh Adri (Al-Mu'tabar, 2021)
ABSTRACT Syekh Muhammad Yasin al-Fadani, a Minangkabau cleric who gained a high position among scholars, both Middle Eastern and Southeast Asian. This study aims to examine the thoughts and contributions of Syeikh Muhammad Yasin Al-Fadani in the field of Hadith studies. The result of this research is that Sheikh Muhammad yasin Al-Fadani is an expert on Hadith sanad who was given the title al-Musnid ad-Dunya, because of his expertise in the field of Hadith, especially regarding the tradition of Hadith. As for his contribution in the field of Hadith is about the Hadith sanad which he poured in the Ijazah sanad which he compiled in many of his books, this sanad diploma allows students of Hadith to find a path that connects to the author of the Hadith book. ABSTRAK Syekh Muhammad Yasin al-Fadani, salah seorang ulama berdarah Minangkabau yang memperoleh kedudukan yang tinggi dikalangan para ulama, baik timur tengah ataupun Asia tenggara. Penelitian ini bertujuan untuk meneliti pemikiran dan kontribusi Syeikh Muhammad yasin Al-Fadani di bidang kajian Hadis. Adapun hasil penelitian ini adalah Syeikh Muhammad yasin Al-Fadani adalah ahli sanad Hadis yang diberi gelar al-Musnid ad-Dunya, karena kepakarannya di bidang Hadis, terutama tentang sanad Hadis. Adapun kontribusinya dalam bidang Hadis adalah tentang sanad Hadis yang beliau tuangkan dalam Ijazah sanad yang beliau susun dalam banyak kitabnya, ijazah sanad ini memungkinkan pelajar Hadis mendapatkan jalur yang tersambung sampai kepada pengarang kitab Hadis tersebut.